(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The areas of supply chain management in vegetable marketing have received significant attention from many researchers. Many of the prior studies have focused on foreign countries in this context, while very few studies have been conducted on the content of the state of Odisha also the majority of the studies have focused on the whole horticulture sector but not specified any particular sector. However, the present study is an attempt to explore the issues and challenges in supply chain management for vegetable marketing regarding the awareness level of young people will be dealt with in this study. The study has been conducted by taking farmers, local commission agents, wholesalers, retailers & consumer responses from Bargarh District. India is the world’s second-largest producer of many vegetables, whereas Odisha ranked fourth in terms of the production of vegetables. Supply chain management plays an important role for the vegetable growers and also for the consumers so that the farmers could be benefited and the consumers could fetch fresh vegetables at the proper price. Vegetable growers are faced many challenges due to limited irrigation facilities and insufficient infrastructure support like cold storage, markets, roads, transportation facilities, etc these are the main reason for low vegetable production. Vegetable crops are more damaged due to heavy post-harvest and handling losses, and high cost of production. For this analysis, the total sample size of farmers is 504, local commission agents 45, wholesalers 67, retailers 84, and the consumer 100 respondents have been selected from that region. This research mainly focuses on the block-level data of the Bargarh district of Odisha. It focuses on the new innovative ideas used for cultivation & marketing. It also focuses on the engagement of youth people and focused produce quality crops at a minimum price.